2013
DOI: 10.1007/s00125-012-2827-3
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the glucose-lowering efficacy of dipeptidyl peptidase-4 inhibitors between Asians and non-Asians: a systematic review and meta-analysis

Abstract: Aims/hypothesis The aim of this work was to compare the glucose-lowering efficacy of dipeptidyl peptidase-4 (DPP-4) inhibitors between Asian and non-Asian patients with type 2 diabetes. Methods We searched MEDLINE, EMBASE, LILACS, CENTRAL, ClinicalTrials.gov and conference proceedings. Studies were eligible if they were randomised controlled trials with a treatment duration of at least 12 weeks, compared a DPP-4 inhibitor with a placebo as either monotherapy or oral combination therapy, had information on ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
343
7
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(383 citation statements)
references
References 82 publications
30
343
7
3
Order By: Relevance
“…HbA 1c was significantly lower at week 52 than at baseline in all groups. DPP-4 inhibitors have a neutral or positive effect on bodyweight [14,15]. We observed a tendency toward weight gain of 0.3 --0.5 kg with monotherapy or combination therapy with a sulfonylurea or glinide at the end of 52 weeks; these differences, albeit small, were statistically significant at the end of 52 weeks.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…HbA 1c was significantly lower at week 52 than at baseline in all groups. DPP-4 inhibitors have a neutral or positive effect on bodyweight [14,15]. We observed a tendency toward weight gain of 0.3 --0.5 kg with monotherapy or combination therapy with a sulfonylurea or glinide at the end of 52 weeks; these differences, albeit small, were statistically significant at the end of 52 weeks.…”
Section: Discussionmentioning
confidence: 62%
“…Overall, there were no clinically significant changes in bodyweight throughout the 52-week period in any groups. Previous studies have shown that higher baseline HbA 1c , lower BMI and shorter duration of diabetes are related to reductions in HbA 1c when using DPP-4 inhibitors in T2DM patients [14,19]. Teneligliptin also produced greater HbA 1c reductions with higher baseline HbA 1c , and slightly improved HbA 1c in patients with lower BMI (< 25 kg/m 2 ), although these patients had lower baseline HbA 1c compared with patients with BMI ‡ 25 kg/m 2 (7.83 ± 0.73 vs 7.94 ± 0.81%, respectively).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies have shown that DPP4is exert greater glycated hemoglobin (HbA1c)‐lowering effects (HLE) in East Asians3, 4. This enhanced efficacy has been attributed to the unique type 2 diabetes phenotype in East Asians, who tend to be non‐obese and to show β‐cell dysfunction2, 5.…”
Section: Introductionmentioning
confidence: 99%
“…This study also reported better efficacy of omarigliptin once weekly than placebo and non-inferiority versus sitagliptin once daily ( Table 1). The results of these two studies obtained in Japanese patients should be replicated in other ethnic groups, especially because DPP-4 inhibitors were shown to exhibit a better glucose-lowering efficacy in Asian than in Caucasian people and because doses of DPP-4 inhibitors may also differ 9 .…”
mentioning
confidence: 96%